2002
DOI: 10.1095/biolreprod.101.000729
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Integrin Expression in the Mouse Ovary1

Abstract: Integrin alpha:beta heterodimers mediate cell contacts to the extracellular matrix and initiate intracellular signaling cascades in response to a variety of factors. Integrins interact with many determinants of cellular phenotypes and play roles in controlling the development, structural integrity, and function of every type of tissue. Despite their importance, little is known about the regulation of integrin subunits in the mammalian ovary and how they function in folliculogenesis. To determine their relevanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…With regard to integrin beta3 in mammalian ovary, few reports have appeared. Burns et al [30] reported that integrin beta3 mRNA was expressed in theca and interstitial cells in mouse ovary, in agreement with our data in the present study. Coincubation with blocking antibody against integrin alpha5 beta3 increased apoptosis and prevented migration in human luteinized granulosa cells grown on fibronectin, suggesting that integrin beta3 might promote survival and migration of granulosa cells [41].…”
Section: Roles Of Thy1 and Integrin Beta3 On Cell Adhesionsupporting
confidence: 94%
See 1 more Smart Citation
“…With regard to integrin beta3 in mammalian ovary, few reports have appeared. Burns et al [30] reported that integrin beta3 mRNA was expressed in theca and interstitial cells in mouse ovary, in agreement with our data in the present study. Coincubation with blocking antibody against integrin alpha5 beta3 increased apoptosis and prevented migration in human luteinized granulosa cells grown on fibronectin, suggesting that integrin beta3 might promote survival and migration of granulosa cells [41].…”
Section: Roles Of Thy1 and Integrin Beta3 On Cell Adhesionsupporting
confidence: 94%
“…An interaction between integrin beta3 and THY1 has been reported to play a role in cell adhesion [27,28]. The mRNA expression of various integrins has been reported in mouse ovaries, and integrin beta3 was found to be expressed only in the theca cell layers in follicles [30]. However, a relationship between THY1 and integrin beta3 function has not been shown in ovaries.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to maintaining the cell-cell connections, cells within three-dimensional environments utilize different integrins and form distinct adhesions with the ECM compared to two-dimensional systems [13], which can affect both cellular organization and tissue function [14]. During follicle development, ECM composition [15] and integrin expression [16] change; however, whether these changes are the result or cause of maturation has not been identified [17]. ECM composition is known to affect granulosa cell differentiation in vitro [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…integrin-deficient mice, demonstrated normal development and fertility [25,29]. We need to verify the localization of vitronectin in the fetal mouse gonads, although the gonadal cells may have another ligand that is recognized by αvβ5 integrin.…”
Section: Discussionmentioning
confidence: 99%
“…PCR consisted of an initial denaturing step of 2 min at 95 C; 33 cycles of 1 min at 95 C, 1 min at 54 C, and 1 min at 72 C for β3 integrin primers; 27 cycles of 1 min at 95 C, 1 min at 58 C, and 1 min at 72 C for β5 integrin primers; and 10 min at 72 C. The primer sequences for β3 integrin were: forward 5'-GTCACATTGGCA-CCGACAACC-3', and reverse 5'-CCACACTC-AAAAGTCCCGTTC-3', which were used to amplify a 556 bp fragment from the mouse β3 integrin cDNA. For β5 integrin, the primers were forward 5'-GGCTGCTGTCT-GCAAGGAG-3', and reverse 5'-TTCAAAGGATG-CCGTGTCC-3', which were used to amplify a 511 bp fragment from the mouse β5 integrin cDNA [25]. As an internal control, we used a housekeeping gene, Gapdh (forward 5'-TGAAGGTCGGTGT-CAACGGA-TTTGGC-3 and reverse 5'-CATGTAGGCCA-TGAGGTCCACC-3').…”
Section: Total Rna Isolation and Rt-pcrmentioning
confidence: 99%